2020
DOI: 10.1177/1066480720973420
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Intervention for Couples Experiencing Infertility: An Emotionally Focused Couples Therapy Approach

Abstract: The psychological and societal intersectionalities of infertility may give way to a complicated pattern of grief, anxiety, depression, and trauma for couples. Current literature on specific interventions for mixed gender couples undergoing infertility treatments notes significant improvements for couples who enact meaning-based coping mechanisms and who have more effective dyadic communication. Emotionally focused couples therapy provides an avenue to engage meaning-based coping strategies proposed by current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Renzi et al similarly showed that men’s higher capability to identify and describe their emotions was associated with their wives’ higher quality of life 39 . It is believed that in dynamic interaction, it is indispensable for couples to make an effort to reduce their partner’s stress by using appropriate strategies 40 . In addition to confirming this recommendation, the results of the present study emphasize that it is required for infertile couples not to share maladaptive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Renzi et al similarly showed that men’s higher capability to identify and describe their emotions was associated with their wives’ higher quality of life 39 . It is believed that in dynamic interaction, it is indispensable for couples to make an effort to reduce their partner’s stress by using appropriate strategies 40 . In addition to confirming this recommendation, the results of the present study emphasize that it is required for infertile couples not to share maladaptive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this conclusion, Nigerian research found that those who follow certain religions or visit the house of worship are less inclined to embrace IVF. This suggests that some people would refuse IVF for the reason that they believed God would supply them with children without the need for any kind of ARTs [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, couple psychotherapy can be offered to couples with relationship problems that go beyond the context of infertility or who present higher psychological distress (i.e., higher levels of depression and anxiety; Gameiro et al, 2015). For example, Emotionally Focused Couple Therapy could help both partners express their emotions, and thus help individuals become more aware of their partner's needs (Brigance et al, 2020), which helps individuals learn PDCS, and thus foster higher relationship satisfaction. In their meta‐analysis, Frederiksen et al (2015) also concluded that cognitive–behavioral therapy would be efficacious for reducing psychological distress in couples seeking fertility treatment.…”
Section: Discussionmentioning
confidence: 99%